Ocular Manifestations and Neuropathy in Type 2 Diabetes Patients With Charcot Arthropathy - Trindade, Marilia; Castro de Vasconcelos, Jessica; Ayub, Gabriel; Grupenmacher, Alex Treiger; Gomes Huarachi, Delma Regina; Viturino, Marina; Correa-Giannella, Maria Lucia; Atala, Yeelen Ballesteros; Zantut-Wittmann, Denise Engelbrecht; Parisi, Maria Candida; Alves, Monica (Frontiers in Endocrinology, 2021)
Objective: Diabetes can affect the eye in many ways beyond retinopathy. This study sought to evaluate ocular disease and determine any associations with peripheral neuropathy (PN) or cardiac autonomic neuropathy (CAN) in type 2 diabetes (T2D) and Charcot arthropathy (CA) patients. Design: A total of 60 participants were included, 16 of whom were individuals with T2D/CA, 21 of whom were individuals with T2D who did not have CA, and 23 of whom were healthy controls. Ocular surface evaluations were performed, and cases of dry eye disease (DED) were determined using the Ocular Surface Disease Index (OSDI) questionnaire, ocular surface staining, Schirmer test, and Oculus Keratograph 5M exams. All variables were used to classify DED and ocular surface disorders such as aqueous deficiency, lipid deficiency, inflammation, and ocular surface damage. Pupillary and retinal nerve fiber measurements were added to the protocol in order to broaden the scope of the neurosensory ocular evaluation. PN and CAN were ascertained by clinical examinations involving the Neuropathy Disability Score (for PN) and Ewing’s battery (for CAN). Results: Most ocular variables evaluated herein differed significantly between T2D patients and controls. When the controls were respectively compared to patients with T2D and to patients with both T2D and CA, they differed substantially in terms of visual acuity (0.92±0.11, 0.73±0.27, and 0.47±0.26, p=0.001), retinal nerve fiber layer thickness (96.83±6.91, 89.25±10.44, and 80.37±11.67 m, p=0.03), pupillometry results (4.10±0.61, 3.48±0.88, and 2.75±0.81 mm, p=0.0001), and dry eye symptoms (9.19±11.71, 19.83±19.08, and 24.82±24.40, p=0.03). DED and ocular surface damage also differed between individuals with and without CA, and were associated with PN and CAN. Conclusion: CA was found to be significantly associated with the severity of ocular findings. DED in cases of CA was also associated with PN and CAN. These findings suggest that intrinsic and complex neurosensory impairment in the eyes, peripheral sensory nerves, and the autonomic nervous system are somehow connected. Thus, a thorough ocular evaluation may be useful to highlight neurological complications and the impact of diabetes on ocular and systemic functions and structures.